Streptomyces pactum and sulfur mediated the rhizosphere microhabitats of potherb mustard after a phytoextraction trial. (15th July 2021) - Guo, Di; Ali, Amjad; Zhang, Zengqiang
Abstract: To explore the performance of Streptomyces pactum (Act12) alone (A) and jointly with sulfur (SA) in the phytoextraction practice of potentially toxic elements (PTEs) (Cd and Zn), as well as their effects on soil chemical properties and microbial community composition, this paper selected potherb mustard ( Brassica juncea, Coss. ) as the test plant to assess the feedback of soil-plant ecosystems. Metal uptake values in lone Act12 treatments were higher than that of Act12 + sulfur treatments, and showed dose dependent with Act12 due to the higher biomass production. According to the biochemical analyses of rhizosphere soils, Act12 inoculation significantly increased urease (20.4%) and dehydrogenase (58.5%) while reducing alkaline phosphatase (68.0%) activity. The production of soil organic acids was, in descending order, formic acid > oxalic acid > malic acid > propionic acid and indicated a stimulated variation under treatments (SA > A > control). High-throughput sequencing revealed that bacterial community compositions were consistent in both phylum and genus taxonomies, while the final overall proportions were modified. The populations of the predominant phyla Proteobacteria and Bacteroidetes increased after sulfur application. The contribution of Act12 to the relative abundance of microbiota was minor compared to sulfur. Based on a redundancy analysis, soil chemical properties are the drivers of microbial activities and the main contributor to plant growth. Our results suggested Act12 inoculation may be part of an effective strategy enhancing phytoremediation of PTE-contaminated soils through chemical and biotic processes, and provided important implications for sustainable land utilization and crop production. Graphical abstract: Image 1 Highlights: Streptomyces pactum activated the production of soil enzymes and organic acids. Both bacterial community structure and diversity were affected by amendments. Streptomyces pactum affected plant rhizosphere, and thereby promoted plant growth. Abstract : Streptomyces pactum and sulfur mediated the rhizosphere microhabitats and thus enhanced phytoextraction of Cd and Zn.